The "taste of life" as a mechanism of overcoming corruption - Ihor Hurnyak; Aleksandra Kordonska (Comparative Economic Research. Central and Eastern Europe, 2018)
The issue of measuring the "taste of life" is one of the main tasks in the process of management decentralization in the state. The term "taste of life" is considered to be the degree of an individual's satisfaction from living, functioning and carrying out his own activity in society in accordance with economic rules and orders. To solve this problem, three approaches were applied by considering the "taste of life" as a function of state authorities' services, shadow activity and communal budget. Based on mathematical modelling and the results of expert surveys in 50 communities in the Ukrainian environment, authors made an attempt to identify the degree of state's regularities in society and to test the constructed models. According to the results, a higher "taste" on the basis of state services caused a decrease in the likelihood of a person returning after the possibility of working and living abroad. The higher "taste" caused the smaller sensitivity to institutes of the shadow economy. At the same time, the "taste" on the basis of shadow services correlates negatively with sensitivity to the state's official engagement in business and penalties for informal activity. So, the higher this segment, the smaller the sensitivity. The behavior of those who consider communal services and the work of the community as a basic variable is quite different. The "taste" on the basis of community services cannot explain the sensitivity to the shadow institutes and dynamics of emigration. Consequently, decentralization is a way of overcoming corruption.
Keywords: C01; D02; H7; H26; P21; 330; taste of life; shadow economy; decentralization; state authority services; community